Kılcal emme mekanizmasının statik ve dinamik koşullarda deneysel incelenmesi - Dönmez, Ayşe (Fen Bilimleri Enstitüsü, 1995)
Doğal çatlaklı rezervuarlarda (DÇR); tek ve çok fazlı akış homojen rezervuarlardakinden büyük farklılıklar gösterir. DÇR'da; yüksek gözenekliliği nedeniyle petrolün büyük kısmı matriks içerisinde yer alırken, akış yüksek geçirgenliğe sahip çatlak tarafından kontrol edilir ve matriksteki petrolü üretebilmek için matriks ve çatlak arasında akışkan transferi olayının gerçekleşmesi gerekir. Doğal bir su itişimi yoksa ve matriks su ıslatımlı ise; matrikste kalan petrolü üretebilmek için; su enjekte edilir ve suyun matriks tarafından emilerek aynı miktar petrolün çatlaklara bırakılması istenir. Bu mekanizmaya kılcal emme (capillary imbibition) adı verilir. Şimdiye kadar; bu olayda etken olan pekçok parametre değişik açılardan incelenmişse de, özellikle kontrol edilebilmesi veya değiştirilebilmesi açısından önemli olan akış ve akışkan özelliklerinin üzerinde daha fazla deneysel çalışmaya gerek duyulmaktadır. Bu nedenle, bu çalışmada akışkan (petrol ve su) ve akış (hızı ve yönü) özelliklerinin emme mekanizmasının verimine olan etkilerinin deneysel olarak incelenmesi hedef olarak belirlenmiştir. Deneyler hem statik hem de dinamik koşullarda gerçekleştirilmiştir. Statik deneyler, iki farklı grup altında ele alınmıştır. Birinci grup deneylerde, sıcaklığın emme ile olan üretim hızı ve kalıcı petrol doymuşluğu; ikinci grup deneylerde ise yüzey aktifleyici maddelerin (surfactant) kalıcı petrol doymuşluğu üzerindeki etkisi incelenmeye çalışılmıştır. Dinamik deneylerde ise; çatlak faktörü de gözönüne alınarak, enjeksiyon hızı, yönü ve çatlak özelliklerinin matriksteki doymuşluk profili üzerindeki etkisi görsel olarak incelenmiştir.

Naturally fractured reservoirs (NFR) contain a substantial share of the oil reserves in the world. A NFR consists of two discrete media: Matrix and fracture. Because of the higher porosity, most of the oil is stored in the matrix but fracture network controls the flow of injected fluid due to its higher conductivity. Under suitable conditions, fluid transfer between fracture and matrix may take place and displacement process differs from homogeneous porous media because of this interaction. The transfer may occur due to capillary suction of water by matrix, if the matrix is water wet. Thus, water can be injected into NFRs to recover matrix oil by the phenomenon called capillary imbibition. Capillary (spontaneous) imbibition is defined as the spontaneous taking up of a liquid by a porous solid due to capillary forces. The capillary imbibition occurs when the fluid filled solid is immersed or brought in contact with another fluid that wets the solid. In this case, the imbibing fluid displaces the non wetting fluid. Some examples of this phenomenon are dry bricks soaking up water and expelling air, sugar soaking up coffee and expelling air and reservoir rock soaking up water and expelling oil. Imbibition may take place if the matrix block is totally or partially immersed into water.. In the case of an oil saturated block totally immersed in water, imbibition rate is given by, g= Pc+g(H-Z)AP (1) ^-[MH + (l-M)Z] Krw" where M is the mobility ratio and given by, (ko/uj XI Eq.l is a function of the difference in magnitude between capillary and gravitational pressure, magnitude of mobility M and of front height Z. As can be seen in Eq.l, if the mobility ratio M is large (this value of M corresponds to highly viscous oil), imbibition rate will decrease. If it is the case, imbibition rate will be increased when the oil viscosity is decreased.. In the case of an oil saturated block partially immersed in water, imbibition rate (u) is given by, Pc + g(Hw-Z)Ap u = ~ (2) -^-[MH + (l-M)Zİ kmkL As long as ZHW gravity will have a retardation effect on the displacement process. Therefore, oil displacement from a block totally immersed into water will occur at a faster rate than oil displacement from a block partially immersed in water. Capillary imbibition rate depends on the following parameters under static conditions.. Matrix wettability: Wettability is the most important parameter in imbibition and the matrix is water-wet, capillary imbibition can take place. The oil production rate by imbibition depends on some function of the contact angle, f(6). In general, the smaller the contact angle, the greater the imbibition rate.. Matrix permeability: As the matrix permeability decreases, capillary forces will increase. The imbibition rate is directly proportional to the square root of the permeability (k).. Interfacial tension: The imbibition rate is directly proportional to the oil- water interfacial tension (EFT).. Oil viscosity: The imbibition rate is the function of the viscosity of both the oil and water. The rate of water imbibition is inversely proportional to the oil viscosity. At a lower oil viscosity, a higher oil recovery will be obtained for the same displacement time. Under dynamic conditions, wetting fluid flowing in the fracture will be imbibed by the matrix and oil will be expelled simultaneously. In this case, the following parameters also affect the mechanism: xn . Injection rate: As the injection rate is increased, the ratio of viscous forces to capillary forces will increase. Thus, water tends to flow in fracture instead of being imbibed by the matrix. In this case, to produce a given amount of oil, more water must be injected.. Fracture density: As the fracture density is increased, the performance of imbibition transfer will increase.. Fracture width: As the fracture width is decreased, the velocity of water in fracture will increase. This causes a decrease in contact time of water with matrix and therefore a stronger imbibition performance will be expected.. Flow direction: If fractures are vertically oriented and water is injected from the bottom, water tends to flow upward and oil tends to flow downward because of the density difference between oil and water. This allows water longer time to contact with matrix resulting in stronger capillary imbibition transfer. The imbibition process has been studied in the past both theoretically and experimentally for various purposes. However, the physics of capillary imbibition and its influence on oil recovery need additional experimental studies because of the complexity of the mechanism. Especially, the effect of fluid and flow properties on the efficiency of capillary imbibition must be studied extensively to clarify the mechanism. As expected, the rate of imbibition substantially decreases by the increasing oil viscosity. Therefore, thermal methods can be applied into NFRs containing heavy oil to reduce viscosity of oleic phase. During application of these processes in NFRs, the following recovery mechanisms may occur: Imbibition Thermal expansion Gas generation Chemical alteration of oil Gravity drainage Alterations of the rock matrix Distillation To investigate the effect of temperature on the imbibition transfer efficiency static experiments were conducted in this study. These experiments were carried out using Berea Sandstone samples with 2.5 cm in diameter and 6.26-7.56 cm in length. Cores were saturated with 5 different types of oil having different properties such as viscosity, IFT, etc., and static imbibition experiments were conducted on these samples. In the first group of experiments, experimental runs were performed at different temperatures under the boiling point of water. Therefore, only imbibition and thermal expansion will be effective mechanisms. Other mechanisms are expected to be effective at higher temperatures, therefore, their influence on oil recovery at the temperature range applied during the experimental runs in this study is negligible. The experimental results showed that imbibition rate and ultimate recovery increased with increasing temperature. The amount of this increase was observed as dependent xiii on changes in both fluid-fluid and fluid-rock properties with temperature and thermal expansion of matrix oil. In the second group of experiments, the properties of water phase were changed by adding surfactant solution to the distilled water instead of NaCl. Using surfactant solution, a set of experiments was performed at ambient temperature. The results showed that the recovery increased by increasing surfactant concentration (or decreasing IFT). Surfactant solution reduces the interfacial tension of oil-water system and this causes a release of trapped oil. Thus, the residual oil saturation decreases and the total oil production by imbibition will increase. When the IFT is very low, both gravity and capillary forces can be important in imbibition mechanisms. The ratio of these two forces can be expressed as, CGR = -^^ = *JL (3) ApgH ApgH This ratio indicates the degree of the contribution of the two forces to the imbibition displacement. CGR directly influences recovery, independent of the other experimental conditions. Recovery is more significant as if CGR is smaller, which shows the role of increased gravitational forces in imbibition. Gravity force is important when the following conditions hold,. If matrix block is very high,. If capillary force is so small, the nominator of Eq.l is very low. We obtain this condition lowering the IFT between the imbibing fluid phase and oil phase, thus the oil recovery by imbibition increases. Dynamic (displacement) experiments were also conducted on fractured 2-D glass bead models to observe the effect of fracture and flow properties on the matrix- fracture transfer. Models were saturated with oil under vacuum and then water was injected through the fracture. In most of the experiments, kerosene-brine fluid pair was used. To investigate the effect of the higher oil water viscosity ratio, engine oil was also used in one experiment. In these experiments, the effects of the injection rate and fracture configuration on the capillary imbibition behavior and saturation distribution in the matrix were visually examined. The injection rate was observed as the most important parameter in this process. Slower rates allowed water longer time to contact with matrix resulting in stronger capillary imbibition transfer. As the injection rate is increased, water tends to flow in the fracture because of its higher conductivity and therefore the performance of imbibition transfer decreases. Also, experiments at the same rates were conducted for different fracture configurations. As the fracture density is increased causing larger matrix fracture contact area, stronger imbibition performance was obtained. Regardless the fracture configuration, at lower rates, the displacement was observed as frontal drive. However, for higher rate applications, the matrix-fracture transfer by imbibition was controlled by fracture xiv configuration. This caused an irregular progress of the water front and non- systematic saturation distributions unlike lower rate cases. It was also concluded that there is a critical rate depending on the matrix properties and above this rate the effect of fracture configuration was felt on the saturation distribution. Below this rate, however, typical frontal drive type displacement occurred. In one experiment, to investigate the effect of flow direction on the imbibition transfer efficiency water was injected through the bottom of the model that was oriented vertically. At the same injection rate, vertical injection case achieved stronger imbibition performance. In this case, water tends to flow upward and oil tends to flow downward of the system because of the density difference between oil and water thus stronger capillary imbibition transfer was obtained. On the other hand, when the model saturated with engine oil having much higher viscosity than kerosene and water was injected into the system, the efficiency of displacement was decreased and viscous fingering type penetration of water into the matrix was observed.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1995
Keywords: Petrol ve Doğal Gaz Mühendisliği; Deneyler; Kılcal emme; Petrol; Petroleum and Natural Gas Engineering; Experiments; Capillary imbibition; Petroleum